3, 1, -1, -3, -5
-2 -2 -2 -2
a(n) = a₁ + d(n - 1)
a(n) = 3 - 2(n - 1)
a(n) = 3 - 2(n) + 2(1)
a(n) = 3 - 2n + 2
a(n) = -2n + 3 + 2
a(n) = -2n + 5
a₁₄ = -2(14) + 5
a₁₄ = -28 + 5
a₁₄ = -23
The answer is C.
Hey there,
<span>Summarize categorical data for two categories in two-way frequency tables. Interpret relative frequencies in the context of the data (including joint, marginal, and conditional relative frequencies). Recognize possible associations and trends in the data.
Hope this answer has helped you...
</span>
The root of an equation is the same as the solution to the equation.
:)